Efficient GBA1 editing via HDR with ssODNs by outcompeting pseudogene-mediated gene conversion upon CRISPR/Cas9 cleavage - Lagas, Joseph S.; Sentmanat, Monica F.; Cui, Xiaoxia (Frontiers in Genome Editing, 2025)
IntroductionCRISPR/Cas9-edited induced pluripotent stem cells (iPSCs) are valuable research models for mechanistic studies. However, gene conversion between a gene-pseudogene pair that share high sequence identity and form direct repeats in proximity on the same chromosome can interfere with the precision of gene editing. Mutations in the human beta-glucocerebrosidase gene (GBA1) are associated with Gaucher disease, Parkinson’s disease, and Lewy body dementia. During the creation of a GBA1 KO iPSC line, we detected about 70% gene conversion from its pseudogene GBAP1. These events maintained the reading frame and resulted from GBA1-specific cleavage by CRISPR/Cas9, without disrupting the GBA1 gene.MethodTo increase the percentage of alleles with out-of-frame indels for triggering nonsense-mediated decay of the GBA1 mRNA, we supplied the cells with two single-stranded oligodeoxynucleotide (ssODN) donors as homology-directed repair (HDR) templates.ResultsWe demonstrate that HDR using the ssODN templates effectively competes with gene conversion and enabled biallelic KO clone isolation, whereas the nonallelic homologous recombination (NAHR)-based deletion rate remained the same.DiscussionHere, we report a generalizable method to direct cellular DNA repair of double strand breaks at a target gene towards the HDR pathway using exogenous ssODN templates, allowing specific editing of one gene in a gene-pseudogene pair without disturbing the other.